Kurdish: Lingua non grata - Κορομπίλη, Αναστασία (Πανεπιστήμιο Πελοποννήσου, 2016)
This dissertation involves at indicating the restriction in the Kurdish community’s linguistic rights from the Turkish state. After the research and study of secondary sources –principally international treaties (e.g Treaty of Sèvres and Lausanne) , domestic legislation( e.g Turkish Penal Code, Administrative legislation and Turkish Constitutions) and Regular Accession Progress Reports by the European Commission we aim at explaining the algebraic linkage between the Turkish nationalism and the Kurdish insurgency and to highlight the restriction of the use and the learning of the Kurdish language as a part of the “big picture”: the Kurdish issue. After explaining fundamental notions over human rights, we dig into the centennial political and legislative history of the Republic; we will identify that the authoritarian Kemalic regime and its lessons for national homogeneity led the policy makers to the designation of a brutal assimilation project, despite the multicultural element of the peoples of the ex-Ottoman territories now leaving within Turkey. Focusing on the political initiatives of Turkey’s politicians from the 1990’s onwards, and principally by presenting the pivotal role of the EU regarding the recognition of certain cultural rights towards the Kurds, we result in the cosmogony of the Helsinki Summit: the recognition of the membership status; parameters that boost the evolution and the democratization process in Turkey. Looking to the EU, Turkey proceeds into massive legislative reforms and constitutional amendments and although it has come a long way, it has even longer and more difficult way ahead.
Κουρδικά:Lingua non grata
Keywords: Κούρδοι--Τουρκία--Πολιτική και διακυβέρνηση; Κούρδοι--Ιστορία; Κούρδοι--Πολιτική και διακυβέρνηση; Μέση Ανατολή--Εθνικές σχέσεις; Γεωπολιτική--Μέση ανατολή; Κούρδοι; Μειονότητες; Κουρδική γλώσσα; Κεμαλισμός; Δικαίωμα μειονοτήτων